Genetic parameters and trends of morphometric traits of GIFT tilapia under selection for weight gain - Reis Neto, Rafael Vilhena [UNESP]; Oliveira, Carlos Antônio Lopes de; Ribeiro, Ricardo Pereira; Freitas, Rilke Tadeu Fonseca de; Allaman, Ivan Bezerra; Oliveira, Sheila Nogueira de (Univ Sao Paolo, 2014)
The main factor considered in breeding programs for fish is growth, which can be assessed in terms of a gain in either weight or body measurements. This study was undertaken to evaluate the morphometric traits of GIFT strain tilapia (Oreochromis sp.) selected for weight gain. The data set used contained information on 6,650 animals. The genetic values of 8,590 animals in a relationship matrix of five generations were predicted. The following morphometric measurements were evaluated: standard length; body depth and body width. Body area and volume were also calculated. Bi-character analyses involving morphometric traits were used to estimate (co)variance components. Heritability, larval and fingerling common environmental effects were estimated for each trait, together with the genetic and phenotypic correlations between traits. Bayesian procedures were utilised by Gibbs chains, and the convergence of the chains was tested using the Heidelberger and Welch method. Genetic trends were estimated by segmented regression of the fish breeding values of the generations considered in this study. Estimates of heritability (0.28 a 0.31) had moderate to high magnitudes for all traits. Genetic correlations between traits were all above 0.8, and the genetic gains were satisfactory from the third generation onwards. From the estimates of the genetic parameters and genetic gain the morphometric traits evaluated have good potential for selection.
Keywords: Bayesian approach; Genetic correlation; Genetic gain; Heritability